A Simulated Dosimetric Study of Contribution to Radiotherapy Accuracy by Fractional Image Guidance Protocol of Halcyon System - Wang, Haiyang; Huang, Yuliang; Hu, Qiaoqiao; Li, Chenguang; Liu, Hongjia; Wang, Xuejuan; Li, Weibo; Ma, Wenjun; Pu, Yichen; Du, Yixiao; Wu, Hao; Zhang, Yibao (Frontiers in Oncology, 2021)
Purpose: Frequency of conventional kV-image guidance is sometimes sacrificed to reduce concomitant risk, leaving deviations of unguided fractions unknown. MV-imaging and treatment dose can be collectively optimized on Halcyon, where fractional MVCBCT provides complete anatomic records for course-wide dose reconstruction. By retrospective dose accumulation, this work simulated the impact of imaging frequency on patient treatment dose on the platform of Halcyon. Methods: Four hundred and sixteen MVCBCT image sets from 16 patients of various tumor sites treated with radiotherapy on Halcyon were retrospectively selected. After applying the image-guided couch shifts of the clinical records, deformable image registration was performed using Velocity software, to deform the planning CTs to the corresponding MVCBCTs, generating pseudo CTs representing the actual anatomies on the treatment day. Fractional treatment dose was reconstructed on pseudo CTs for accumulation, representing the actual patient dose (D_daily). To simulate weekly image guidance, fractional dose was reconstructed and accumulated by incorporating 1 CBCT-guided corrections and 4 laser-guided setups of each week (D_weekly). Limited by partially imaged volumes and different organs-at-risk of various sites, only target dose-volume parameters were evaluated across all patients. Results: GTV_D98%, CTV_D98%, PTV_D90%, PTV_D95%, PGTV_D90% and PGTV_D95% were evaluated, where Dx% means the minimal dose received by x% volume. Pairwise comparisons were made between plan dose and D_daily, D_daily and D_weekly respectively. PGTV_D_(95%)of accumulated D_weeklywere significantly lower than those of accumulated D_daily by up to 32.90% of prescription dose, suggesting that weekly-guidance may result in unacceptable under dose to the target. The broad distribution of fractional differences between D_daily and D_weekly ¬suggested unreliable patient positioning based on aligning surface markers to laser beams, as a popular approach broadly used on conventional Linac systems. Slight target under-dose was observed on daily reconstructed results compared with planned dose, which provided quantitative data to guide clinical decisions such as the necessity of adaptive radiotherapy. Conclusion: Fractional image guided radiotherapy on Halcyon provides more reliable treatment accuracy than using sacrificed imaging frequency, which also provides complete anatomic records for deformable dose reconstruction supporting more informed clinical decisions.